Imam Sheikh Al-Allamah Al-Qadi Hussein bin Mohsen Al-Ansari Al-Yamani, his life and scientific efforts: الإمام الشيخ العلامة القاضي حسين بن محسن الأنصاري اليماني حياته وجهوده العلمية - Channar, Dr. Hafiz Mehmood ul Hassan; Ahmed Khan, Prof. Dr. Hafiz Munir; Ahmed Khan, Prof. Dr. Ubaid (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
The religion of Islam is the only true religion acceptable to Allah. It guarantees the success of both worlds. There are two basic sources of Islamic teachings: Quran and Hadith. One cannot learn both off them without knowledge. Those having such knowledge are called Ulama or scholars. Scholars of Islam have left no stone unturned to preach Islam and convey its message all over the world. These scholars belonged to various parts of the world. Yemen is also one of the lands which were centers for knowledge of Islam. It is the land of great scholars and Islamic institutions. People from parts of the world travelled to this land to seek knowledge and learn Islamic teachings. Shiekh Husain Bin Muhsin al-Yamani was one of the scholars who belonged to this land. He was born in Hudaidah, Yemen, in the year 1245 A.H. He was a great scholar and taught many students. He was appointed as judge and wrote many books. Here is list of his famous books: al-Tuhfatul Marzia, al-Bayanul Mukmal, al-Fathul Rabbani, Iqamatul Hujjah, and Fatawa, etc. His services will always be remembered by scholars of Islam. He died in year 1327 .